THE EFFECT OF COMPENSATION, ORGANIZATIONAL COMMUNICATION, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE (CASE STUDY ON CIVIL SERVANTS OF THE DOWNSTREAM OIL AND GAS REGULATORY AGENCY) - Sukrasno, Sukrasno; Elmi, Farida (Dinasti Publisher, 2021)
This study aims to examine and analyze the effect of compensation, organizational communication, and job satisfaction on the performance of Civil Servants at the Downstream Oil and Gas Regulatory Agency. The research sample used the criteria of a permanent employee in a company/organization. The sampling method was carried out by probability sampling with a total of 132 samples. The data collection technique used a questionnaire. Methods of data analysis using SEM-PLS. The results of this study indicate that compensation has a significant positive effect on employee performance, organizational communication has a significant positive effect on employee performance, job satisfaction has a significant positive effect on employee performance, and compensation, organizational communication, and job satisfaction simultaneously have a positive effect on employee performance.